Simone Cimotto, The Italian American Table. Food, Family, and Community in New York City (Altre Modernità, 2015)
Simone Cimotto, The Italian American Table. Food, Family, and Community in New York City(Urbana, Chicago, and Springfield, University of Illinois Press, 2013, pp. 265,ISBN 978-0-252-07934-4)